Cucurbitacin B induces oral squamous cell carcinomapyroptosis via GSDME and inhibits tumour growth - Xin Chen; Mengyuan Yang; Heng Zhang; Yajun Wang; Wenpeng Yan; Chen Cheng; Rongrong Guo; Jiawei Chai; YaHsin Zheng; Fang Zhang (Translational Oncology)
Background: Pyroptosis, a form of programmed cell death, has been shown to induce anti-tumour immunity and inhibit tumour growth. Oral squamous cell carcinoma (OSCC), a prevalent malignant tumour, could benefit from pyroptosis induction as a therapeutic strategy. Cucurbitacin B (CuB), a natural compound derived from various plants, exhibits broad anti-tumour activity. However, whether CuB can exert its anti-tumour effects in OSCC through pyroptosis remains unexplored. Results: CuB significantly inhibited the proliferation of OSCC cells, induced pyroptosis, and elevated the levels of inflammatory factors in the cell supernatant. Bioinformatics analysis predicted the potential role of pyroptosis in OSCC, which was subsequently validated in a 4NQO-induced OSCC mouse model. The results demonstrated that CuB not only exerted tumour-inhibitory effects but also increased the infiltration of CD8+ T cells in the peritumoural region. To elucidate the mechanism of CuB-induced pyroptosis, STAT3 was identified as a key target of CuB in OSCC, with its expression upregulated in tumour tissues. Further experiments revealed that CuB induced pyroptosis by suppressing STAT3 expression and promoting the cleavage of caspase-3 and Gasdermin-E (GSDME). Conclusion: CuB triggers OSCC pyroptosis through the STAT3/caspase-3/GSDME pathway, enhancing peritumoural CD8+ T cell infiltration and offering a novel strategy to boost tumour immunotherapy efficacy.